Factors associated with help-seeking for emotional or mental health problems in community members at risk of suicide. (2nd September 2021) - Mok, K.; Chen, N.; Torok, M.; McGillivray, L.; Zbukvic, I.; Shand, F.
ABSTRACT: Objective: People experiencing mental health problems or suicidal thoughts often do not seek help. This study aims to investigate factors associated with help-seeking behaviours for emotional and mental health problems in individuals at risk for suicide. Method: A community sample was recruited online through Instagram and Facebook advertisements. There were 4277 participants in total, aged 18–84 (72.8% female, 26.8% male and .4% other), of which 1306 were classified as low/medium risk of suicide and 572 as high risk. Regression analyses examined factors associated with past year help-seeking from four categories of help: informal help, general practitioner, mental health professional, and tele/e-health. Predictors included: age, gender, exposure to suicide, psychological distress, suicidal ideation, and knowledge of and attitudes to suicide. Results: Overall, rates of help-seeking increased as risk for suicide increased. Higher levels of suicidal ideation were associated with a greater likelihood of having previously sought help from a GP and mental health professional, but a lower likelihood of having sought help from informal sources. Younger age was associated with past year help-seeking from informal sources and tele/e-health sources. Men had a significantly lower likelihood of having sought help from general practitioners. Different dimensions of attitudes towards suicide were also found to be associated with different types of help-seeking. Discussion: Understanding the characteristics and patterns of different forms of help-seeking can have important implications for the development of effective suicide prevention strategies.